Scientific Parallelism in Personnel Mobility Research: A Preview of Two Approaches - Boehm, Virginia R. (Academy of Management Review, 1981)
Two articles—one by Anderson, Milkovich, and Tsui, the other by Stumpf and London—address the study of mobility within organizations from different perspectives. Both are motivated by societal as well as theoretical concerns, but the models and propositions developed in the two papers are more different than they are similar. Anderson et al. take a broader approach to intra-organizational mobility, but the propositions they offer are less testable than those of Stumpf and London.